Striped domains of coarse-grained magnetite observed by X-ray photoemission electron microscopy as a source of the high remanence of granites in the Vredefort dome - Kubo, Hiroto; Nakamura, Norihiro; Kotsugi, Masato; Ohkochi, Takuo; Terada, Kentaro; Fukuda, Kohei (Frontiers in Earth Science, 2015)
The characteristics of a coarse-grained high-remanence magnetite obtained from shocked Vredefort granite were investigated by X-ray magnetic circular dichroism (XMCD) analysis and X-ray absorption spectroscopy (XAS). The study utilized a spectroscopic photoelectron low-energy electron emission microscope (SPELEEM) and was conducted in the SPring-8 large-synchrotron radiation facility. It is generally believed that the strong and stable bulk remanence of Vredefort granites is due to the presence of minerals that have been strongly magnetized by either an impact-generated magnetic field or terrestrial lightning strikes. Although coarse-grained magnetite is traditionally characterized by weak coercivity and remanence, the specimen used in the present study exhibited high coercivity and an intense remanent magnetization. The presence of hematite lamellae observed on the partially oxidized magnetite specimen indicated an array of striped domains, intensifying a remanence and coercivity. We also conducted XAS and XMCD analyses on a natural lodestone permanent magnet produced by lightning strikes; while maghemite was found to be present, no magnetic domain structures were observed. Considering that the nucleation of hematite lamellae on magnetite/maghemite grains is due to high-temperature oxidation, we attribute the intense remanent magnetization and magnetic hardening of Vredefort granites to post-impact hydrothermal activity.